Multi-session online interpretation bias training for anxiety in a community sample. (July 2021) - Ji, Julie L.; Baee, Sonia; Zhang, Diheng; Calicho-Mamani, Claudia P.; Meyer, M. Joseph; Funk, Daniel; Portnow, Samuel; Barnes, Laura; Teachman, Bethany A.
Abstract: The present study assessed target engagement, preliminary efficacy, and feasibility as primary outcomes of a free multi-session online cognitive bias modification of interpretation (CBM-I) intervention for anxiety in a large community sample. High trait anxious participants ( N  = 807) were randomly assigned to a CBM-I condition: 1) Positive training (90% positive-10% negative); 2) 50% positive-50% negative training; or 3) no-training control. Further, half of each CBM-I condition was randomized to either an anxious imagery prime or a neutral imagery prime. Due to attrition, results from six out of eight sessions were analyzed using structural equation modeling of latent growth curves. Results for the intent-to-treat sample indicate that for target engagement, consistent with predictions, decreases in negative interpretations over time were significantly greater among those receiving positive CBM-I training compared to no-training or 50-50 training, and vice-versa for increases in positive interpretations. For intervention efficacy, the decrease in anxiety symptoms over time was significantly greater among those receiving positive CBM-I training compared to no-training. Interaction effects with imagery prime were more variable with a general pattern of stronger results for those completing the anxious imagery prime. Findings indicate that online CBM-I positive training is feasible and shows some promising results, although attrition rates were very high for later training sessions. Highlights: Free online CBM-I training targeting anxiety delivered to the community. Positive training is better than 50-50 and No-training at changing interpretations. Anxiety reduction was greater in those receiving Positive training than No-training. Attrition was very high. of the N  = 807 sample, N = 105 completed six training sessions, N  = 89 completed seven sessions, and N  = 26 completed all eight sessions.